Exopolysaccharide from Lacticaseibacillus paracasei alleviates gastritis in Helicobacter pylori-infected mice by regulating gastric microbiota - Yu, Jianxing; Chen, Ziqi; Zhou, Qingqing; Li, Ping; Wu, Shiying; Zhou, Tao; Gu, Qing (Frontiers in Nutrition, 2024)
In this paper, a Lactic acid bacteria (LAB) strain with good exopolysaccharide (EPS) producing ability, namely, Lacticaseibacillus paracasei ZFM54 (L. paracasei ZFM54) was screened. The fermentation conditions of L. paracasei ZFM54 for EPS production were optimized. The EPS54 was characterized by chemical component and monosaccharide composition determination, UV, FT-IR and NMR spectra analysis. Cango red, SEM, AFM and XRD analysis were conducted to characterize the structure of EPS54. The EPS54 effectively reduced the colonization of Helicobacter pylori to AGS cells and recovered the cell morphology. EPS54 could also effectively alleviate the gastritis in the H. pylori-infected mice by down-regulating the mRNA expression levels of pro-inflammatory cytokines IL-6, IL-8, IL-1β and TNFα and up-regulating the mRNA expression of inflammatory cytokine IL-10 in gastric cells. EPS54 was also found to be able to positively regulate the structure of gastric microbiota. The present work provides new insights into the anti-H. pylori effect of the EPS produced by L. paracasei.